The language of szmonces as a sub-code of the Jewish humorous tales - Tymiakin, Leszek (Papers in Linguistics, 2019)
This article explains the following terms: ‘szmonces’, ‘humour’, ‘comicality’, and ‘anecdote’. It proposes a register of over 30 linguistic properties that distinguish a standard version of Polish from the spoken language used by the first generation of assimilated Jews, living in Poland during the interwar period. The author discuses a Jewish diaspora, often characterized by the above mentioned sub-code, with a focus on: a) people – their weaknesses, strengths, professions, and (b) everyday objects used in shtetlekh as well as a range of events and concepts that influenced the everyday of people of the Jewish faith. The paper concludes with a list of functions of “szmonces” which reach beyond the sub-code, such as: identification, humour, education, and popularization.